Ascorbic acid functionalized CdS–ZnO core–shell nanorods with hydrogen spillover for greatly enhanced photocatalytic H2 evolution and outstanding photostability. Issue 15 (6th April 2021) - Sun, Guotai; Xiao, Bing; Zheng, Hong; Shi, Jian-Wen; Mao, Siman; He, Chi; Li, Zhihui; Cheng, Yonghong
Abstract : In this work, a new kind of CdS–ZnO core–shell nanorods with controlled ZnO shell are first synthesized by a simple chemical deposition method in aqueous solution. Abstract : In this work, a new kind of CdS–ZnO core–shell nanorods with controlled ZnO shell are first synthesized by a simple chemical deposition method in aqueous solution. The thickness and distribution of the ZnO shell can be accurately adjusted, and intimate contact interfaces between CdS and ZnO are well constructed. The optimal CSZ0.5 core–shell heterostructure exhibits a photocatalytic H2 evolution rate of 805.5 μmol h −1 without co-catalysts (3 mg of catalyst, equal to 268.5 mmol g −1 h −1 ), which is 12 and 895 times higher than that of CdS and ZnO, respectively, and is the maximum value among CdS-based photocatalysts under similar experimental conditions. The significant enhancement in the photocatalytic H2 evolution rate can be mainly attributed to three positive factors: the single-crystalline structure of CdS, the Z-scheme mechanism formed between CdS and ZnO, and the introduced ascorbic acid. The first two factors effectively promote the separation and migration of charge carriers, and the latter factor realizes efficient hydrogen spillover for CdS/ZnO to accelerate the photocatalytic hydrogen evolution reaction. In addition, the homogeneous ZnO shell grown on the CdS core efficiently suppresses the photo-corrosion of CdS, which endows CdS/ZnO with outstanding photostability.